Redefining the subcultural: the sub and the cultural - Erik Hannerz (Educare)
Arguing against the previous research’s presumption that the subcultural constitutes a single set of meaning, this article addresses the simple question of what constitutes the subcultural? What does it mean when we address an object, practice, identity, or meaning structure as subcultural? Through outlining three dominant strands in regards to how subcultural difference has been defined, the author argues that the previous research on subcultural theory has been preoccupied with a definition of subcultures as being a response to external structural problems, with the result that both the “sub” and the “cultural” become dependent variables. Drawing from his work on punks in Sweden and Indonesia the author argues that although differing, the different strands in regards to subcultural difference can nevertheless be combined into a refinement of subcultural theory that moves beyond style to how objects, actions, and identities are communicated, interpreted, and acted upon. Such a refinement, the author argues, provides for an analysis of plurality within the subcultural in relation to multiple structures of meaning. An increased focus on the prefix sub and its relation to the root cultural allows for a discussion of how the subcultural is symbolically extended and more so, how this involves both conflict and alternative interpretations.